Entrepreneurship - Lambing, Peggy A (Prentice Hall, 1997)
This introduction to entrepreneurship covers the effects of change in the international business environment. It includes chapters on starting, buying, franchising, home-based businesses and family businesses. The emphasis is on the effects of self-employment and his or her family.